2013
DOI: 10.1155/2013/782941
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO Blood Group and Major Cardiovascular Risk Factors with Coronary Heart Disease

Abstract: The purpose of this study is to establish whether ABO blood group is related to coronary heart disease in an individual in Asian Indian Bengali population of eastern part of India. Two hundred and fifty (250) CHD patients and two hundred and fifty (250) age and sex matched healthy subjects were enrolled in the study. ABO blood group distribution in patients was compared with control group. Frequency of major cardiac risk factors was determined to find any correlation between blood groups and cardiovascular ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 13 publications
3
35
2
Order By: Relevance
“…Like us other researchers from other countries also came to same conclusion that AB blood group reduces risk of coronary heart disease (CHD) due to the higher concentration of HDLc and O blood group increases the risk of CHD as a result of lower HDLc in Bengali population of eastern India. 17 Our results are also strengthened by some studies that have suggested that people with A blood group have high total cholesterol (TC) and low density lipoprotein cholesterol (LDLc) levels than the other blood types. 24 Our results are also supported by previously published studies in which the non-O blood group members have been shown to have greater concentrations of Von Will brand clotting factors.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Like us other researchers from other countries also came to same conclusion that AB blood group reduces risk of coronary heart disease (CHD) due to the higher concentration of HDLc and O blood group increases the risk of CHD as a result of lower HDLc in Bengali population of eastern India. 17 Our results are also strengthened by some studies that have suggested that people with A blood group have high total cholesterol (TC) and low density lipoprotein cholesterol (LDLc) levels than the other blood types. 24 Our results are also supported by previously published studies in which the non-O blood group members have been shown to have greater concentrations of Von Will brand clotting factors.…”
Section: Discussionsupporting
confidence: 73%
“…7 Many studies have previously linked ABO and Rh blood groups with several non-communicable diseases such as diabetes, hypertension and myocardial infractions. 4,5,[8][9][10][11][12][13][14][15][16][17][18][19] Although several studies have linked incidences of stroke with the inheritance of ABO blood groups also however these results have not been consistent. [20][21][22] Therefore in the current study we decided to look at relationship between the occurrence of hemorrhagic stroke and the ABO blood groups in Saudi adult male population.…”
mentioning
confidence: 99%
“…[4][5][6][22][23][24][25] Although according to many recently published findings people with O blood groups are at increased risk of coronary artery diseases as compared to subjects who have inherited non-O blood groups (A, B, and AB). 26,27 According to few other studies individuals with blood groups other than the O blood group (A, B, or AB) may be at higher risk of dying from MI and the other cardiovascular disease (CVD) related complications however the exact biological mechanisms that are involved for causing this increased heart disease risks remains unclear. In an earlier study, mortality associated with the ischemic heart disease was more common among non-O blood groups (A, B, AB).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been published showing the association between the inheritance of blood groups (ABO and Rh antigens) and cardiovascular diseases [8][9][10], coronary artery disease [7], ischemic heart disease (IHD) [11], however results have not been consistent. According to one study as compared to the other blood groups A blood group subjects had significantly high risk of IHD [11], while another study suggests AB blood groups reduce the risks of CHD while O blood groups raise the risks of CHD due to lower HDL-c levels [10].…”
Section: Introductionmentioning
confidence: 99%